PHYSICAL FIELDS OF CIRCULAR CYLINDRICAL PIEZOCERAMIC RECEIVER IN PRESENCE OF A FLAT ACOUSTIC SOFT SCREEN - A. V. Derepa; A. G. Leiko; O. N. Pozdniakova (Приборы и методы измерений, 2017)
System in the form of a circular cylindrical piezoceramic transducer near a flat acoustic screen was analyzed. The aim of the work was to solve the problem of receiving plane sound waves by «cylindrical piezoceramic transducer – flat acoustically soft screen» system.Considered system was characterized by a violation of the radial symmetry of the radiation load of the transducer while maintaining the radial symmetry of the electric load. At the same time, the energy perceived by the system under consideration is distributed between all modes of oscillation of the transducer, while the conversion of mechanical energy into electric is realized only at zero mole of oscillations.Special attention was paid to the method of coupled fields in multiply connected domains using the imaging method. The design model of the «transducer–creen» system was formulated taking into account the interaction of acoustic, mechanical and electric fields in the process of energy conversion, the interaction of a cylindrical transducer with a flat screen and the interaction of a converter with elastic media outside and inside it. The physical fields of the system under consideration were determined by following solutions: the wave equation; equations of motion of thin piezoceramic cylindrical shells in displacements; equations of stimulated electrostatics for piezoceramics for given boundary conditions, conditions for coupling fields at interfaces and electrical conditions.A general conclusion was made concerning solving of an infinite system of linear algebraic equations with respect to the unknown coefficients of the expansion of the fields. As an example of the application of the obtained relations, a calculation was made and an analysis of the dependences of the electric fields of the system under consideration for various parameters of its construction on the direction of arrival on the plane wave system was conducted.